Hospital Management Information System Implementation Assessment Using HOT-FIT Model in Langsa General Hospital Aceh, Indonesia - Sri Wahyuni Nasution; Chairunnisa Chairunnisa (Majalah Kedokteran Bandung, 2023)
In providing the best health care to the community, hospitals as health care facilities utilize technologies that are influenced by developments and advances in medical sciences and technologies. One of such technologies is the information management technology. Since the quality of information processing is an essential factor for succesful medical care of patients, Regulation of the Minister of Health of the Republic of Indonesia Number 82 of 2013 requires all hospitals to implement a hospital information management system (HIMS). To assess the successful implementation of HIMS, various models and frameworks have been developed, including the HOT-FIT model. This study aimed to analyze the implementation of the hospital management information system at Langsa General Hospital, Aceh, Indonesia, using the HOT-FIT model which applied the SEM-PLS method. This quantitative study was performed in approximately three months using the HOT-FIT (company, technology-FIT human,) framework that includes nine variables of system quality, information quality, service quality, organization structure, facility situations, support from leadership, system usage, user satisfaction, and net benefits. Data analysis was performed using the SEM-PLS analysis in SmartPLS application (V.3.2.9). Results showed that human, organization, and technology supports were factors that influence the successful implementation of HIMS. To conclude, the HOT-FIT model can be used to identify the factors that influence the successful implementation of HIMS to inform the HIMS improvement in the hospital that will eventually improve the hospital’s quality system, information, service quality, and user satisfaction.